High-moisture extrusion of soy protein: Effects of insoluble dietary fiber on anisotropic extrudates. (August 2023) - Deng, Qian; Wang, Zhaojun; Fu, Liwei; He, Zhiyong; Zeng, Maomao; Qin, Fang; Chen, Jie
Abstract: Insoluble dietary fiber (IDF) was commonly present in feedings during extrusion for preparing plant protein-based meat analogs. The aim of this study was to investigate the feasibility of using IDF to improve the fibrous structure of high-moisture extrudates (HME) produced from soybean protein isolate (SPI). The structures of extrudates were analyzed visually and using confocal laser scanning microscopy (CLSM) and scanning electron microscopy (SEM). The mechanical properties of extrudates were determined by a texture analyzer. The CLSM and SEM images of SPI-IDF extrudates presented a clear interface between the SPI and IDF domains, which indicated that the IDF phase dispersed within the SPI phase reduce the mutual cross-linking between SPI. The substitution of 10%–20 wt% IDF promoted the formation of an SPI matrix/IDF filler mesh structure, which could contribute to the fibrous appearance and higher mechanical anisotropy. Substitution of more IDF in SPI resulted in a collapsed structure, possibly due to macroscopic phase separation during extrusion. It can be concluded that the partial substitution of SPI with IDF can promote the formation of a fibrous structure with enhanced mechanical anisotropy. Graphical abstract: Image 1 Highlights: The addition of IDF in SPI enhances the mechanical anisotropy of extrudates. IDF facilitates the formation of filamentous structures in extrusion. IDF addition increases the storage modulus of SPI-IDF blends. Phase separation of SPI and IDF is likely to occur during extrusion.